2019
DOI: 10.1088/2057-1976/ab49f5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous contra-lateral radiometric asymmetry in the diabetic patient

Abstract: We introduce a methodology for acquisition and analysis of infrared (IR) images, picturing the metabolic heat emission from the human skin. Then we analyze the radiometric asymmetries in the patients with DM2 in comparison to the natural asymmetries, represented by the control group. In this regard, we introduce three indices (TAI, SAI, TtAI) with conditions for disclosing asymmetries displayed on images acquired in passive mode (the natural thermal emission, NTE). Then, the indices are adapted for analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…According with the ROC-analysis, except for the TAI, that conserves its diagnostic performance (89% of sensitivity and 72% of specificity) with and without noise, indices SAI and TtAI change their performances as follows: for the SAI the specificity increases from 67% to 72%, and the sensitivity remains in 78%; in the case of the TtAI the specificity remains in 78% and the sensitivity increases from 83% to 88% [5].…”
Section: Fig 7 Results Of the Subtraction Between The Asymmetry Indmentioning
confidence: 99%
See 4 more Smart Citations
“…According with the ROC-analysis, except for the TAI, that conserves its diagnostic performance (89% of sensitivity and 72% of specificity) with and without noise, indices SAI and TtAI change their performances as follows: for the SAI the specificity increases from 67% to 72%, and the sensitivity remains in 78%; in the case of the TtAI the specificity remains in 78% and the sensitivity increases from 83% to 88% [5].…”
Section: Fig 7 Results Of the Subtraction Between The Asymmetry Indmentioning
confidence: 99%
“…The task is to achieve a large and reliable IRI data base. The details on the methodology for the thermal asymmetry study are reported in [5]. In the current work we produce a comparative study, by getting information from a region of interest (ROI) of the IRIs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations